The Effect of Branding Quality and Service Quality on Customer Satisfaction through Financial Technology (FinTech) at PT. WOM Finance Branch Rantauprapat - Fani Pramaswari; Ade Parlaungan Nasution; Siti Lam’ah Nasution (Budapest International Research and Critics University, 2021)
In today's digital era, service companies are competing to improve the quality of their companies. By providing good service to make it easier for consumers to be more loyal, one form of strategy that is currently being carried out by service companies. PT WOM Finance provides a much better service to further increase consumer loyalty to the company through Financial Technology (Fintech), which currently WOM Finance is much better for its branding. The influence of quality is what will make it easier for them to get maximum results every month. This research was conducted by means of the Normality assessment test with five variables of Branding Quality, Service Quality, Customer Satisfaction, and the Intervening Fintech Variable with the number of respondents as many as 150 customers. The results of this study indicate that partially the quality of branding, service quality on customer satisfaction through financial technology has a significant effect on customer participation by increasing the company's profit.